Kwanongoma College of the Rhodesian Academy of Music (International Library of African Music, 1965)
Four years ago, only one performer on the Marimba (African Xylophone) could be found in the Bulawayo African Townships and he was an old man. In August this year, no less than 70 young people at one of the Youth Clubs gave performances on these instruments, under the guidance of their teacher, a graduate from Kwanongoma.
Keywords: African Music; Rhodesia; Zimbabwe